A Legal Politics of the Criminal Justice System in Dealing with Cybercrime in the Era of Digital Transformation to Realize Justice in Criminal Law Enforcement in Indonesia - umar umar dinata; Ike Sumawaty (Equality Before The Law, 2026)
Digital transformation has changed the patterns and characteristics of crime to become increasingly complex, organized, and cross-jurisdictional, posing new challenges for the criminal justice system in Indonesia. Adaptive legal politics is the main prerequisite to ensure that criminal law policies can accommodate technological developments while ensuring legal certainty, justice, and utility. This research aims to analyze the legal politics of the criminal justice system in dealing with cybercrime in the era of digital transformation and to reconstruct criminal law policies to realize justice in criminal law enforcement in Indonesia. The research uses a juridical-normative method with a legislative and conceptual approach. The research data is in the form of secondary data obtained through literature studies on laws and regulations, scientific literature, and previous research results, then analyzed qualitatively by descriptive-systematic analysis techniques. The results of the study show that the legal politics of the criminal justice system still face various obstacles in the form of regulatory disharmony, limitations in electronic evidence arrangements, weak coordination between law enforcement, and suboptimal protection for victims of cybercrime. Therefore, the reconstruction of criminal law policy needs to be directed at harmonizing regulations, strengthening restorative justice, protecting victims, digitizing the criminal justice system, increasing the capacity of law enforcement officials, and strengthening national and international cooperation. The reconstruction is expected to be able to realize a criminal justice system that is adaptive, fair, oriented towards the protection of human rights, and responsive to the development of digital technology